Open government in Spain: An introspective analysis - Ricardo Curto-Rodríguez; Rafael Marcos-Sánchez; Daniel Ferrández (Administrative Sciences, 2024)
In recent years, there has been an increasing amount of research analyzing open government initiatives that enable access to the information held by public bodies, promoting accountability and the fight against corruption. As there are few studies on intermediate governments to date, this research focuses on this level of government in Spain, one of the most decentralized countries in the world. The autonomous communities in Spain manage over 35% of consolidated public spending and are responsible for providing most social services, including health, education, and social services. To achieve this goal, the perceptions of the seventeen heads of open government in Spain's autonomous communities were collected through a questionnaire. This approach fills a research gap as individuals outside of public administration have made the previous assessments. By allowing for a comparison with the conclusions reached by prior research, this study contributes to the creation of new knowledge. The study's results are consistent with previous research and suggest that the open government in Spain is positively regarded, not falling below the European or global averages, and has a promising future despite significant obstacles, such as a resistance to change. Transparency is the most developed aspect of open government, while citizen collaboration ranks last. The autonomous communities of the Basque Country, Aragon, Castile Leon, and Catalonia have been identified as the most advanced in terms of open government. The analysis did not reveal any gender-based differences in opinion. Still, it did show variations based on age, the size of the autonomous community, or membership to the most developed group. Therefore, it is evident that promoting open government in the autonomous communities of Spain should continue.
Keywords: 350; accountability; collaboration; open government; public administrations; transparency